2020
DOI: 10.1108/bfj-09-2019-0746
|View full text |Cite
|
Sign up to set email alerts
|

Sub-national consumer ethnocentrism and the importance of the origin of food products: an exploratory analysis

Abstract: PurposeThis study's main objective is to analyse the role of the consumer's ethnocentrism as a potential segmentation basis and to detect product origin-sensitive groups. The relationship between the consumer's regional ethnocentrism, local and regional identity and corresponding valuation and purchase of food products from a region is also examined.Design/methodology/approachThe responses of 358 consumers residing in two Spanish regions are analysed by means of a mediation analysis and a cluster analysis.Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 36 publications
(43 reference statements)
2
26
1
1
Order By: Relevance
“…That circumstance can affect its capacity to moderate other effects. Compared with the values reported by Fernández‐Ferrín, Bande, Martín‐Consuegra, Díaz, and Kastenholz (2020) for regional identity in Galicia (Mean = 5.57; SD = 1.30) this study's sample shows a higher value and lower variability for this variable.…”
Section: Data Analysis and Resultscontrasting
confidence: 81%
“…That circumstance can affect its capacity to moderate other effects. Compared with the values reported by Fernández‐Ferrín, Bande, Martín‐Consuegra, Díaz, and Kastenholz (2020) for regional identity in Galicia (Mean = 5.57; SD = 1.30) this study's sample shows a higher value and lower variability for this variable.…”
Section: Data Analysis and Resultscontrasting
confidence: 81%
“…The "classical" type of consumer ethnocentrism, at the national level, was examined. It is also possible to study this phenomenon at the subnational level [28,49]. Similar to previous research in Poland [50], the CETSCALE item that buying foreign-made food was not patriotic received the lowest support in the sample.…”
Section: Discussionsupporting
confidence: 51%
“…Conversely, consumers often avoid buying foreign products when they do not have sufficient information about them (Farah and Mehdi 2021). Moreover, some studies (Fernández-Ferrín et al 2020;Bianchi and Mortimer 2015), have shown that consumer ethnocentrism can vary among different regions of the same country and that it has a strong influence in purchasing local or regional products, because consumers want to support local economy. This is particularly evident when consumers buy regional or local labelled products, such as Protected Designation of Origin, Protected Geographical Indications and Traditional Specialty Guaranteed (Oleniuch and Cichocka 2015) products or local sustainable fruits and vegetables (Boca 2021), because, by means of their consumption, they contribute to the sustainable development or rural areas.…”
Section: Consumer Ethnocentrism Literaturementioning
confidence: 99%